RONCHI TEST AND TRANSVERSAL SAN LUIS POTOSIHERICAL ABERRATION - MALACARA HERNANDEZ, D (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1969)
Ronchi test is extremely useful to determine the quality of optical systems that have transversal spherical aberrations even in the case of being perfectly well built. The purpose of this work is to describe a method to compute the ronchigram of any syste
BOL OBS TONAN TACUB
Keywords: RONCHI TEST, TRANSVERSAL, SPHERICAL, ABERRATION; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS